ORIGIN, CLINICAL COURSE AND TREATMENT OF ACUTE MIDDLE OTITIS - Akramov A. S.; Norboev Z. K. (Galaxy International Interdisciplinary Research Journal, 2024)
Purulent-inflammatory diseases of the ear, throat, nose and upper respiratory tract are among the most common – on average, they affect at least 75% of the human population. The problem of adequate diagnosis, rational treatment and rational prevention of these diseases remains relevant for a wide variety of specialists – from otolaryngologists to health organizers; the integrated approach to its solution is based on combining different areas of knowledge, from molecular biology to hygiene and sanitation. Acute purulent inflammation of the middle ear is a very common otiatric disease. The frequency of this disease is 25-30% of the total number of ear diseases. According to American authors, hearing loss of the US population occurs in 60% of cases due to acute purulent otitis in childhood.